Physiological response to professional road cycling: climbers vs. time trialists - Lucia, A.; Joyos, H.; Chicharro, J. L. (International Journal of Sports Medicine, 2000)
The purpose of this study was to identify possible physiological differences between professional cyclists who show best performance in hill climbing ("climbers") and those who excel in time trials ("time trialists"). To this end, professional, top-level climbers (C; n=8; age 26 +/- 1yr; height 176.0 +/- 2.0cm; body mass 63.6 +/- 2.2 kg) and time trialists (TT; n=6; 27 +/- 1yr; height 181.6 +/- 1.7 cm; body mass 72.3 +/- 2.3 kg) were required to perform two laboratory exercise tests on a cycle ergometer: a) a maximal exercise test (ramp protocol) and b) a constant load test of 20-min duration at approximately 80% of VO2max. Capillary blood lactate concentration and several gas exchange variables were measured during the maximal tests while determinations made during the submaximal tests also included: pH and bicarbonate concentration [HCO3-] in venous blood, and electromyographic (EMG) recordings from the vastus lateralis muscle to estimate root mean square voltage (rms-EMG) and mean power frequency (MPF). Both the maximal lactate concentration in capillary blood and VO2max were greater (p<0.05) in C than in TT (6.6 +/- 0.9 mM vs. 5.0 +/- 0.4 mM, respectively, and 78.4 +/- 3.2 ml x kg(-1) x min(-1) vs. 70.5 +/- 2.4 ml x kg(-1) x min(-1), respectively). Higher mean venous blood pH and [HCO3-] (p<0.05), rms-EMG (p<0.01) and MPF (p<0.05 at 10 and 15min of exercise and p < 0.01 at 5 and 20 min) were recorded in C throughout the submaximal tests. Our findings suggest that in top-level professional cyclists, climbing performance is mainly related to physiological factors (VO2max normalized for body mass, anaerobicl buffer capacity, motor unit recruitment) whereas time trialists tend to achieve greater absolute power outputs. It would also seem that other "technical" requirements of the sport (i. e. pedaling efficiency probably related to biomechanical factors etc.) may be associated with successful time trial performance.